Talking of... Dientamoeba fragilis - Giulia Zorzi (Microbiologia Medica, 2013)
Introduction: Dientamoeba fragilis is a protozoan parasite of human gastrointestinal tract with worldwide distribution and a controversial pathogenic role. Data on prevalence and geographical distribution are underestimated for difficult microscopic recognition and “fragility” of the protozoan. Generally to perform the O & P exam for identification of D. fragilis it is necessary to recur to a permanent stain and to an expert microscopist. Methods: we analyzed fecal samples of 3907 patients enrolled among the patients referred to the Service of Microbiology of Padova University Hospital for routine parassitology examinations from June 2011 to June 2012. The aim of this study was to document the prevalence and the clinical features of D. fragilis infection. The laboratory detection rate of the organism is greatly enhanced by use of preservative to fix stool specimens immediately after passage. As previously described for a rapid identification of D. fragilis, in unstained fixed fecal material by direct microscopy (400X), the demonstration of the characteristic “golf-club” and “acanthopodia-like” structures are suitable. Results: in this study the prevalence was found to be 6.8%, higher than our previous reports. Out of the 267 patients in which we detected D. fragilis, 26.0% presented with extra-intestinal symptoms, 19.8% reported gastrointestinal complaints and 17.0% referred abdominal pain. Conclusions: D. fragilis, even if considered a neglected parasite, is not rare and the presence of this fecal agent is associated to various intestinal and probably systemic clinical symptoms, even though asymptomatic carriers have been reported. D. fragilis infects in high rates among close household contacts; so the Authors stress the importance of screening close contacts to prevent re-infections after treatment.